KAJIAN PENDEKATAN REHABILITASI LAHAN KRITIS MELALUI PENGEMBANGAN MAMAR - Fransiskus Xaverius Dako; Fabianus Ranta; Ika Kristinawanti (Politeknik Pertanian Negeri Kupang, 2008)
dy on Rehabilitation Approach of Critical Farm by Exploiting of Mamar. Mamar is one of the permanent agricultural practises developed around a water source, using long-aged plants (hard plants), such as, coconuts, battle, mango, bananas, oranges and others as well as brushes or grasses for animal feeds. Practise of mamar in Kupang Regency is still communal so that development model of this can give positive impacts on safety of human activities and fire. The research was executed at mamar in Oebola, Camplong, Tuatuka, Pukdale, Oenesu, and Manulai villages, Kupang Regency, for 8 months, using survey and interview methods. Survey was conducted to find out characteristic ecosystem of mamar (soil, vegetation, climate, exploiting, and water). The result indicated that vegetations found at mamar covered Tectona grandis, Artocapus integra, Ficus benjamina, Tamarindus indica, Bamboo sp, Leucaena leucochepala, Mangifera indica, Cocos nucifera), Arecha catechu , Mozes parasidica, Zea mays, Dioschorea sp, and Arachis sp. Exploiting of soil, water, and vegetations at mamar was very abundant to various activities, such as, food and horticultural agriculture, and fishery that potentially, could degrade soil productivity, water infiltration, plasma nutfah reserve, and degrade income value and ecology improvement. Volume of water at mamar was 0.23Â±0.09 L/sec. These results showed that mamar can increase community income (that increase Â± Rp 262,985), social and culture (it is due to the use of battle and battle nut in traditional life); rehabilitate critical/poor soil, and conserve soil and water.Keywords: mamar, log-aged plants, rehabilitation.